DISASTER RISK REDUCTION AND SOCIAL JUSTICE FRAMEWORK IN INDONESIAN LAW: FROM NATIONAL TO LOCAL REGULATION - Lita Tyesta Addy Listya Wardhani; Amalia Diamantina; Athanasius Allan Darma Saputra (Faculty of Law, Universitas Diponegoro, 2026)
This study examines the extent to which disaster risk reduction (DRR) law incorporates social justice as a normative foundation. It argues that disaster law, particularly within the contemporary DRR paradigm that prioritises prevention, resilience, and collaborative governance, must move beyond technical risk management and embed justice in both substance and procedure. Social justice in disaster governance is conceptualised through four interrelated dimensions: distributive justice, procedural justice, human rights, and good governance. Drawing on Alexy’s theory of the ideal dimensions of law, the study contends that the legitimacy of disaster law should not rest solely on formal validity, but also on its orientation toward substantive justice. To assess the realisation of social justice, this study develops an analytical framework consisting of five indicators derived from those dimensions: protection of vulnerable groups, equitable disaster funding, access to disaster-related information, meaningful public participation, and institutional accountability. Using qualitative legal research with a doctrinal approach, the study applies this framework to international, national, and sub-national instruments, including the Sendai Framework for Disaster Risk Reduction, Indonesian Law No. 24 of 2007 on Disaster Management, and Lampung Province Regional Regulation No. 6 of 2024 on Disaster Management. The findings show that these legal frameworks generally recognise elements of social justice, yet significant normative and institutional gaps remain. Vulnerable groups are often defined in broad and static terms, insufficiently reflecting intersecting factors such as gender, disability, age, socioeconomic status, and geographical marginalisation. In addition, participation is commonly acknowledged as a principle, but is rarely supported by clear mechanisms that guarantee meaningful community involvement in decision-making. Strengthening these indicators is essential to transform disaster law into a justice-oriented framework capable of protecting vulnerable populations and advancing DRR objectives.